STRATEGI PEMASARAN WARUNG KOPI DI KOTA MEDAN DENGAN GAME THEORY - Imsar Imsar; Marliyah Marliyah; Faisal Hamdani Harahap (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
Existence of coffee shops now in the Medan city has greatly increased. Of course this triggers competition between coffee shops, so that every coffee shop owner must think about their efforts to face their competitors. Then an optimal marketing strategy is needed. To determine the optimal marketing strategy, game theory is used using the 7P marketing mix strategy, namely Product, Price, Place, Promotion, People, Process and Physical Evidence. The coffee shops that are the object of this study are the DWS Coffee Shop and the Khup Kupi Coffee Shop. In assessing the marketing strategies used by each coffee shop, the researcher distributed a questionnaire to a number of coffee shop customers, therefore the researcher used Probability Sampling. The analysis technique used is descriptive test, validity test, reliability test and game theory which are processed using POM QM 5.0. From the results of the research that has been tested, it was found that the DWS Coffee Shop won the Price, Process, and Physical Evidance strategy, while the Khup Kupi coffee shop won the Product, Place, Promotion and People strategy. In this study, the results showed that both coffee shops have a saddle point of 788, which means that the two coffee shops have tight competition. And in this study also according to the results of the test results of the DWS Coffee Shop and Khup Kupi Coffee Shop simultaneously using Physical Evidance with points of 1 indicated.